Willow Project Socialization As An Introduction To Petroleum Engineering At Yos Sudarso Metro High School - Prayang Sunny Yulia; Apriandi Rizkina Rangga Wastu; Arinda Ristawati; Pauhesti Pauhesti; Ridha Husla; Gracia Betaria Jacqueline Timpal; Puri Wijayanti; Reza Aryanto; Widia Yanti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
The Willow Project is located on Alaska's north slope, within the National Petroleum Reserve, which is held by the United States federal government. Based on the topics being discussed, a strong desire was developed, particularly among Yos Sudarso Metro High School students, to learn about the causes for oil drilling, as well as the impacts and benefits of drilling from diverse perspectives. Concerning the community service that according to Willow Project theme, the lecturers as the facilitators of this community service assisted students who wanted to find a solution to the Willow Project issue, where they hoped that there would be several points regarding the impact and benefits of academia in the energy sector, particularly petroleum engineering. As a result of socialization regarding the Willow Project drilling, impacts and benefits have been imparted in the Community Service activities, which are separated into environmental impacts, climate impacts, and social impacts. Following an overview of the impact of the Willow Project drilling, the benefits of the drilling are explained, including job creation and economic benefits, energy independence, and tax revenue. The crux of the impacts and benefits given is that it is still envisaged that fossil energy would be used to increase jobs in the nearby community and globally. Aside from that, it is desired that the development of renewable energy, the reduction of drilling in conservation areas, and the preservation of environmental integrity would continue.